A solar-assisted hybrid air-cooled adiabatic absorption and vapor compression air conditioning system. (15th December 2021) - Chen, Erjian; Chen, Jinfeng; Jia, Teng; Zhao, Yao; Dai, Yanjun
Highlights: Experimental and simulated investigation of solar-assisted air conditioning system. Adiabatic absorption cycle is proposed to accommodate air-cooled design. Performance comparison between cascade mode and subcooling mode are conducted. COPele of the subcooling mode increases by 29.8%. COPele of the cascade mode increases by 166.7%. Abstract: Absorption-compression hybrid systems which consist of absorption and vapor compression cycle have advantages on both energy efficiency and cost-effectiveness. In the open literature, a great amount of research on such hybrid systems focuses on the water-cooled system which requests a larger area for the whole cooling unit due to the size of the cooling tower. In this paper, an air-cooled solar-assisted hybrid system consists of an adiabatic absorption (ABS) and a vapor compression refrigeration system (VCR) with subcooling mode and cascade mode is proposed for miniaturization. Steady-state experiments of the proposed system in the cascade mode were carried out and subsequently a numerical model is developed to evaluate performance difference and possible application for the two kinds of coupled modes. Simulation results show an increment of 63.9%∼166.7% in the electric COP of the system ( COPele, sys ) in the cascade mode, which is similar to from the experimental findings. Although the simulated COPele, sys increases by only 15.9% ∼ 29.8% in the subcooling mode, electricity saving rate brought by unit thermal energy input (defined as 'r') and the exergetic efficiency ( COPex, sys ) are significantly greater than those of the cascaded mode. So is the primary energy efficiency ( PEE ). It is concluded that the subcooling mode driven by the compound parabolic collector (CPC) is applicable to residential buildings due to its distinct advantages —— lower levelized cost of cooling ( LCOC ) of 0.06 US /kWh, shorter payback time ( PBT ) of 8.54 years and smaller collector area of 11.41 m 2, in comparison with other configurations. The study of this paper can function as guidance for design of the air-cooled absorption-compression integrated air conditioning system.